Boundary and ethnicity: Slovenian-Croatian boundary on Mura and around Štrigova and Razkrižje - Josipovič, Damir (Anali PAZU, 2022)
This contribution deals with the Slovenian-Croatian boundary at its north-eastern extremity, represented by the course of Mura River and its surroundings. The author discusses the river boundary on Mura, its role in the contemporary boundary dispute, as well as about the function of this boundary in the formative processes of Slovene and Croat ethnic space. The article analyzes deviations and inconsistencies between the main Mura River course and the cadastral mapping of the boundary on both sides of the disputed area. Along with the cartographic representations and perceptions of the boundary course from both Slovenian and Croatian points of view, the problems of terrestrial delimitation around Štrigova and Razkrižje, and Mura riverbed with its backwater and branches respectively, are set forth. Grounding in these spatial and historical- geographic developments the function of the border as the determinant of an ethnic divide is explained as well.
Keywords: political geography; Slovenian-Croatian boundary dispute; Mura; Hotiza